2019
DOI: 10.1108/wje-06-2019-0170
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of machining parameters under MQL turning of Ti-6Al-4V alloy with textured tool using multi-attribute decision-making methods

Abstract: Purpose This paper aims to focus on the application of multi-attribute decision-making methods (MADMs) to ascertain the optimal machining parameters while turning Ti-6Al-4V alloy under minimum quantity lubrication (MQL) conditions using Jatropha-curcas oil (JCO) bio-based lubricant. Design/methodology/approach The experiments were designed and performed using Taguchi L27 design of experiments methodology. A total of 27 experiments were performed under MQL conditions using textured carbide cutting tools on wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The results indicated that the two methods TOPSIS and SAW respond similarly, the optimal values of the cutting speed, feed rate and depth of cut are 80 m/min, 0.05 mm/rev and 0.1 mm, respectively [22].…”
Section: Introductionmentioning
confidence: 93%
“…The results indicated that the two methods TOPSIS and SAW respond similarly, the optimal values of the cutting speed, feed rate and depth of cut are 80 m/min, 0.05 mm/rev and 0.1 mm, respectively [22].…”
Section: Introductionmentioning
confidence: 93%
“…A combination method of Taguchi and Grey relational analysis (GRA) was used to optimize the turning process of DIN 1.2344 steel [28], turning the unidirectional glass fiber reinforced plastic (UD-GFRP) composite rods [29], turning the EN-8, EN-31 steel and EN-36 steel [30], turning the DIN Ck45 steel [31]. Taguchi was combined to TOPSIS and SAW method to optimize the turning process of Ti-6Al-4V alloy under minimum quantity lubrication (MQL) [32]. Taguchi was also combined to GA and PSO algorithm to optimize the turning process of S45C steel [33].…”
Section: Introductionmentioning
confidence: 99%
“…Selecting the cutting parameters to simultaneously ensure the minimum values of surface roughness, cutting forces, flank wear, where weights of parameters were determined by decision-makers [12]. Study [13] was performed to determine the cutting parameters to simultaneously ensure the minimum values of surface roughness, cutting forces, flank wear, and cutting temperature, where the weights of the criteria were determined by the AHP method. Selecting the cutting parameters to simultaneously ensure the minimum value of surface roughness and maximum value of MRR, where weights of parameters were determined by decision-makers [12].…”
Section: Introductionmentioning
confidence: 99%